Agroforestry form and ecological adaptation in ancient Hawai'i: Extent of the pākukui swidden system of Hāmākua, Hawai'i Island. (May 2020) - Lincoln, Noa Kekuewa
Abstract: Agricultural strategies in ancient Hawai'i were adaptive, occasionally unique, and increasingly being shown to have strongly related to the local environmental opportunities and constraints. However, little is known about the extent of arboriculture and forest modification due to the lack of physical infrastructure and remains associated with these forms of agriculture. We utilize historical ethnography and remote sensing to examine the form and function of agroforestry along the Hāmākua coast on Hawai'i Island. Mapping over 26, 000 remnant trees of two species used in Hawaiian agroforestry systems, we identify two distinct applications of arboriculture: A permanent arboricultural system with substantial breadfruit ( Artocarpus altilis (Parkinson) Fosberg) and a shifting cultivation system based on candlenut ( Aleurites moluccanus (L.) Willd). The distributions of these systems on the landscape appear to be constrained by soil fertility and temperature, with the swidden agricultural system occurring on the more fertile portion of the landscape and the permanent arboricultural system occupying the less fertile lands. Experimentation demonstrating the nitrogen accumulation and fixation associated with candlenut compost suggests that the swidden system would be maximized if the rotation occurred in the range of 6–12 years Highlights: Despite historical disturbance, the use of remnant trees to understand ancient arboriculture in Hawai'i appears valid. On the Hāmākua coast of Hawai'i two distinct forms of agroforestry existed and thier distribution related to soil fertility. Hawaiian geopolitical boundaries align with the ecology and geography of the different forms of agroforestry. Swidden cultivation in local candlenut forests rapidly accumulate nitrogen with small contributions from nitrogen fixation.